Cut-off points to screening for sarcopenia in community-dwelling older people residents in Brazil - Sabrina Gabrielle Gomes Fernandes; Luiz Eduardo Lima de Andrade; Rafaella Silva dos Santos Aguiar Gonçalves; Saionara Maria Aires da Câmara; Ricardo Oliveira Guerra; Alvaro Campos Cavalcanti Maciel (PeerJ, 2021)
Background At a time when the world’s population is aging, one of the most important challenges for the healthcare field is to control the decline of the musculoskeletal system. This decline consists of a reduction in muscle mass and function, which is called sarcopenia and is associated with adverse health outcomes. Although there has been an increase in the number of publications on sarcopenia and its consequences, the reported prevalence varies widely, since these depend on the characteristics of the population studied, the definitions found in the literature and the cut-off points adopted. In this perspective, the heterogeneity in the classification and the different reference values has a critical impact on the epidemiology of sarcopenia, since neither the procedures, the components and the cut-off points are consistent. Objectives To develop cut-off points for the screening of sarcopenia in community-dwelling older people residents in the northeast of Brazil and compare the prevalences between the values defined by the consensus and the values of the population studied. Methods Community-dwelling older men and women living in three cities in the countryside of Rio Grande do Norte were evaluated. Cutoff points were defined for the variables used to screen for sarcopenia (handgrip strength, SMI, gait speed and SPPB) using the 20th percentile of their population distributions. Results The sample was composed of 1,290 older people (62.5% female and 37.5% male), with an average of 69.5 (± 6.05) years of age. Regarding the cutoff points, the handgrip values were defined as 25.3 kg and 16 kg for men and women, respectively. Considering the SMM adjusted according to their height, the values of 7.88 kg/m2 were adopted for men and 5.52 kg/m2 for women. When adjusting by BMI we obtained 0.73 kg/BMI for men and 0.41 kg/BMI for women. For gait speed it was defined 0.71 m/s for men and 0.63 m/s for women. In the case of SPPB, the result was the same for both genders (≤8). When applying the values found in the studied population, a variation in prevalence was observed for both men and women, depending on the cut-off points and consensus used. Conclusion The cutoff values found in our population were lower than those adopted by international consensus (EWGSOP2, IWGS and FNIH), except for HGS in woman and SMI/m2 for men. Therefore, using specific cutoff points for different populations can provide an accurate assessment of the presence of sarcopenia and better target health prevention strategies for the older people living in the community.